Endothelium-mediated contributions to fibrosis. (May 2020) - Sun, Xuetao; Nkennor, Blessing; Mastikhina, Olya; Soon, Kayla; Nunes, Sara S.
Abstract: Fibrosis, characterized by abnormal and excessive deposition of extracellular matrix, results in compromised tissue and organ structure. This can lead to reduced organ function and eventual failure. Although activated fibroblasts, called myofibroblasts, are considered the central players in fibrosis, the contribution of endothelial cells to the inception and progression of fibrosis has become increasingly recognized. Endothelial cells can contribute to fibrosis by acting as a source of myofibroblasts via endothelial-mesenchymal transition (EndoMT), or by becoming senescent, by secretion of profibrotic mediators and pro-inflammatory cytokines, chemokines and exosomes, promoting the recruitment of immune cells, and by participating in vascular rarefaction and decreased angiogenesis. In this review, we provide an overview of the different aspects of fibrosis in which endothelial cells have been implicated.